Effectiveness of circulo massage on fatigue recovery of boarding school students - Abdulloh, Faza Muhamad Tamyiz; Rahayu, Atikah; Kushartanti, B. M. Wara; Ivanov, Danail; Jurek, Joanna Michalina (Tanjungpura Journal of Coaching Research, 2026)
Background. Circulo massage was claimed to be effective for fatigue recovery. This massage technique is meant to improve blood flow to the body's extremities. This helps move and get rid of metabolic waste products while also relaxing muscles and nerves. However, there was still a lack of evidence with student as the research subjects. Objectives. Therefore, this study was designed to see the effectiveness of circulo massage in decreasing fatigue among boarding school students. Methods. The study design used in this research was a pre-experimental one with a one-group pretest–posttest design. The subjects were the students of IJ Al-Masyhuriyyah Complex of Al-Munawwir Krapyak Islamic Boarding School, Yogyakarta. The population in this study were 41 students while the samples were 15 students. The data in this research were collected using the Fatigue Assessment Scale (FAS) as the pretest and posttest to determine the fatigue condition. The data analysis was performed using a paired t-test to obtain the amount of change and the significance of the changes in fatigue levels after circulo massage was given. Results. Circulo massage treatment reduced the fatigue scores of the subjects ((Mpre = 35.93 ± 6.67, Mpost = 19.07 ± 4.33, p < 0.001). This result shows that the circulo massage had a statistically significant effect for fatigue recovery. Conclusion. The result of this study can be used as a reference by the students in choosing a treatment or intervention to reduce fatigue due to their daily activities as a student and boarding school student life. This study also provided information about scientific evidence in the massage effect for fatigue recovery.